2018
DOI: 10.3329/bjms.v17i1.35291
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ayarij Faiqura in Qarah-e-Hazmiya - Randomized controlled Clinical study

Abstract: Background and Objective: Qarahe Hazmiya (Peptic ulcer disease) is one of the commonest ailment of Gastro intestinal tract, reported to affect around 4% of the population and 10% of people developed it at some point in their life. Etiopathology of the disease is considered as multi factorial mostly treated with medications and rarely with surgery. Several Unani formulation have been indicated effective in Qarahe Hazmiya, one of such formulation has been selected to evaluate its efficacy and to validate the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The effect of the study was assessed with reference to 0th day, 7th, 14th, 21st, and 28thdays and observed a change in the mean difference with standard deviation in objective parameter. 108 Siddha: Siddha Varmam and Thokkanam therapy (SVT) in the treatment ofadhesive capsulitis (Kumbavatham) this study was conducted.…”
Section: Physiotherapymentioning
confidence: 99%
“…The effect of the study was assessed with reference to 0th day, 7th, 14th, 21st, and 28thdays and observed a change in the mean difference with standard deviation in objective parameter. 108 Siddha: Siddha Varmam and Thokkanam therapy (SVT) in the treatment ofadhesive capsulitis (Kumbavatham) this study was conducted.…”
Section: Physiotherapymentioning
confidence: 99%